Social Media's Impact on Indomart - D Yadi Heryadi; I Nyoman Tri Sutaguna; Norvadewi Norvadewi; Arief Yanto Rukman; Akhmad Nur Zaroni (Lembaga Pengembangan Kinerja Dosen, 2023)
The impact of buying panic is not easy on Indomart. The study aims to analyze the impact of panic purchases on unplanned purchases in Indomart stores. This research uses quantitative parallels with the type of explanatory research. The sample of the study consisted of 193 respondents and was statistically processed using a simple linear regression method using the SPSS version 26.0 application. That research shows that panic purchases influence unfair purchases at Indomart stores. The findings indicate that the anxiety and fear experienced by the people at the time of the landlord's concern for the needs of the household caused the occurrence of panic purchases. It relates to the quality of the goods and the needs of the individuals in the community to meet their daily needs so as to counteract unplanned buying tendencies at the time of shopping at Indomart stores.